Identifying key transcription factors and immune infiltration in non-small-cell lung cancer using weighted correlation network and Cox regression analyses - Zhang, Jingyao; Wang, Yinuo; Yuan, Baowen; Qin, Hao; Wang, Yong; Yu, Hefen; Teng, Xu; Yang, Yunkai; Zou, Jun; Zhang, Min; Huang, Wei; Wang, Yan (Frontiers in Oncology, 2023)
Lung cancer is one of the most common cancers and a significant cause of cancer-related deaths. Non-small cell lung cancer (NSCLC) accounts for about 85% of all lung cancer cases. Therefore, it is crucial to identify effective diagnostic and therapeutic methods. In addition, transcription factors are essential for eukaryotic cells to regulate their gene expression, and aberrant expression transcription factors is an important step in the process of oncogenesis in NSCLC. We identified 725 differentially expressed transcription factors between NSCLC and normal tissues by analyzing mRNA profiling from The Cancer Genome Atlas (TCGA) database program. Three highly related modules for survival were discovered, and transcription factors highly associated with survival were obtained by using weighted correlation network analysis (WGCNA). Then line plot of least absolute shrinkage and selection operator (LASSO) was applied to screen transcription factors related to prognosis and build a prognostic model. Consequently, SETDB2, SNAI3, SCML4, and ZNF540 were identified as prognosis-related transcription factors and validated in multiple databases. The low expression of these hub genes in NSCLC was associated with poor prognosis. The deletions of both SETDB2 and SNAI3 were found to promote proliferation, invasion, and stemness in lung cancer cells. Furthermore, there were significant differences in the proportions of 22 immune cells between the high- and low-score groups. Therefore, our study identified the transcription factors involved in regulating NSCLC, and we constructed a panel for the prediction of prognosis and immune infiltration to inform the clinical application of transcription factor analysis in the prevention and treatment of NSCLC.